Effect of nanocellulose isolation techniques on the formation of reinforced poly(vinyl alcohol) nanocomposite films - H. Y. Zhan; Y. M. Zhou; L. M. Zheng; S. Y. Fu (eXPRESS Polymer Letters)
Three techniques including acid hydrolysis (AH), 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO)-mediated oxidation (TMO) and ultrasonication (US) were introduced to isolate nanocellulose from microcrystalline cellulose, in order to reinforce poly(vinyl alcohol) (PVA) films. Important differences were noticed in fiber quality of nanocellulose and film properties of PVA nanocomposite films. The TMO treatment was more efficient in nanocellulose isolation with higher aspect ratio, surface charge (–47 mV) and yields (37%). While AH treatment resulted in higher crystallinity index (88.1%) and better size dispersion. The fracture surface, thermal behavior and mechanical properties of the PVA nanocomposite films were investigated by means of scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and tensile testing. The results showed that both the TMO-derived and AH-derived nanocellulose could be dispersed homogeneously in the PVA matrices. AH/PVA films had higher elongation at break (51.59% at 6 wt% nanocellulose loading) as compared with TMO/PVA, while TMO/PVA films shown superior tensile modulus and strength with increments of 21.5% and 10.2% at 6wt% nanocellulose loading. The thermal behavior of the PVA nanocomposite films was higher improved with TMO-derived nanofibrils addition.